Tri-iodo-L-thyronine Promotes the Maturation of Human Cardiomyocytes-Derived from Induced Pluripotent Stem Cells - Yang, Xiulan (2014)
BACKGROUND: Cardiomyocytes derived from human induced pluripotent stem cells (hiPSC-CMs) have great potential as a cell source for therapeutic applications such as regenerative medicine, disease modeling, drug screening, and toxicity testing. This potential is limited, however, by the immature state of the cardiomyocytes acquired using current protocols. Tri-iodo-L-thyronine (T3) is a growth hormone that is essential for optimal heart growth. In this study, we investigated the effect of T3 on hiPSC-CM maturation. METHODS AND RESULTS: A one-week treatment with T3 increased cardiomyocyte size, anisotropy, and sarcomere length. T3 treatment was associated with reduced cell cycle activity, manifest as reduced DNA synthesis and increased expression of the cyclin-dependent kinase inhibitor p21. Contractile force analyses were performed on individual cardiomyocytes using arrays of microposts, revealing an almost two-fold higher force per-beat after T3 treatment and also an enhancement in contractile kinetics. This improvement in force generation was accompanied by an increase in rates of calcium release and reuptake, along with a significant increase in sarcoendoplasmic reticulum ATPase expression. Finally, although mitochondrial genomes were not numerically increased, extracellular flux analysis showed a significant increase in maximal mitochondrial respiratory capacity and respiratory reserve capability after T3 treatment. CONCLUSIONS: Using a broad spectrum of morphological, molecular, and functional parameters, we conclude that T3 is a driver for hiPSC-CM maturation. T3 treatment may enhance the utility of hiPSC-CMs for therapy, disease modeling, or drug/toxicity screens.